Effect of electron injected air on the gasification performance of biomass. (1st April 2022) - Ismail, Tamer M.; Yoshikawa, Kunio; Kobori, Takahiro; Kobayashi, Yoshinori; Kanazawa, Kiryu; Takahashi, Fumitake; Abd El-Salam, M.
Highlights: The gasification reaction of biomass was enhanced by injecting electrons into air. The electron injection had a considerable impact on the pyrolysis process. The electric field enhancing the gasification and volatile flow (CO, H2 and CH4 ). The amount of tar decreased in the electron-ON case. Abstract: The mathematical modeling and the experimental study employing the pilot-scale up-draft fixed bed gasifier were carried out to investigate the effect of the electron injected air on the performance of biomass gasification. The goal of the mathematical modeling was to illustrate the temperature and chemical composition fields. Moreover, the stream function provided by the electron injected air to the flame, and to consider its effect on the development of the flame reaction zone. The results obtained showed that the electron injection generated the electric field, which enhanced the flame's stability greatly. The influence of the flame reaction zone generated by the field-induced ionic wind on the thermal breakdown of biomass was explored, as well as the improvement mechanism of gasification properties by the electric field.